Coffee Farmers' Adaptation to Climate Change in Pamatang Sidamanik (Case Study: Pamatang Sidamanik District, Simalungun Regency, North Sumatra) - Ramainim Saragih; Andrian Yosia Marpaung; Jhonson A Marbun; Sry Artawati (Jurnal Penelitian Pendidikan IPA, 2025)
This research is based on the fact that recently there have been frequent changes in weather compared to previous years, according to data from the Central Statistics Agency (BPS) of Simalungun Regency, it does not show major climate changes but has changed the perception of coffee farmers towards climate change in Pamatang Sidamanik District. This research was located in 3 villages in Pamatang Sidamanik District, namely Pamatang Sidamanik, Bandar Manik, and Sait buttu Saribu. The research method used was qualitative and quantitative, with data collection through questionnaires, interviews, and observations of 60 farmers selected purposively. Research data was measured using a Likert scale and analyzed using the Spearman correlation test and multiple linear regression. The results of this study are based on the frequency of farmers' perceptions, some farmers perceive changes in climate components as the same as before, although some farmers stated that there have been changes. When associated with climate components, it turns out that the perception of coffee farmers is that rainfall has increased, rainy days have increased, and minimum temperatures have increased. While maximum temperatures, air humidity, and sunlight intensity are moderate or the same as before. Mitigation measures as an effort to adapt to climate change by planting shade trees. Changes in all climate components are perceived to have a negative impact on coffee plants, for changes in air temperature, rainfall and rainy days are minimized through mitigation actions by farmers, while other climate components are not significant or real. The results of multiple linear regression analysis show that simultaneously the ratio of coffee plants to shade, fertilizer costs, labor costs and land area affect coffee farming income but partially only labor costs affect coffee farming income.